Gandhian Democratisation in Nationalism - Narasingha Charan Panda, (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
Mohandas Karamchand Gandhi is widely known as Mahatma Gandhi due to his noble personality, true sacrifice & great contribution to Indian freedom movement.  Gandhi encouraged simplicity in life, abhorred violence and had enough charisma to inspire the masses. This paper tries to examine the nature of Gandhian political ideas about Gandhian democratisation in nationalism and what were these meant for Gandhi and His future vision for India. The paper is divided into 4 parts: i. Gandhi’s democratization; ii. Gandhi’s civilisational democratization; iii. Individual and community in Gandhi’s point of view and iv. State and swaraj.Received 9thDecember 2020; Revised 2nd March 2021; Accepted 18th March 2021